Brazil's Long-Term Growth Performance-Trying to Explain the Puzzle - Adrogue, Ricardo (IMF Working Papers; Working Paper ;, 2006)
This paper assesses Brazil's growth performance from a long-term perspective, using crosscountry and panel estimation techniques, building on the vast empirical literature on growth. The empirical evidence presented in this paper confirms that macroeconomic stability and several reforms have helped raise per capita growth in Brazil since the mid-1990s. The results also show that some long-standing structural weaknesses continue to weigh negatively on per capita growth. Reducing the high level of government consumption would help lower the overall consumption level in the economy and lower its intertemporal price-the real interest rate-thus helping to foster investment and growth.